Correlation between Neutrophil-to-Lymphocyte Ratio and Severity of Community-Acquired Pneumonia in Patients - Almira, Naufalia Ghina; Hasan, Helmia; Wardhani, Puspa; Hernaningsih, Yetti; Bintoro, Siprianus Ugroseno Yudho; Romadhon, Pradana Zaky (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2025)
The high morbidity and mortality rates due to pneumonia in developing countries indicate that a more affordable marker is needed to determine the degree of inflammation in cases of pneumonia infection. The neutrophil-to-lymphocyte ratio (NLR) is a simple indicator used extensively in evaluating the systemic inflammatory response. An observational cross-sectional study of 297 pneumonia patients was conducted using medical records as the source document. The patients’ blood was taken during the hospital admission to obtain neutrophil and lymphocyte values. Meanwhile, the PSI score was used during the hospital admission to assess the severity of the pneumonia. Bivariate analysis using Spearman correlation was used to determine the correlation between NLR and pneumonia severity. The ROC curve was used to determine the cut-off value of NLR to distinguish mild from severe patients. The results of the Spearman correlation test analysis showed that the correlation between the NLR and the pneumonia severity was significantly positive (r = 0.130; p = 0.025). Furthermore, the median NLR value was higher in patients with severe pneumonia than in those with milder pneumonia severity (13.01 vs. 11.79 vs. 6.75). The NLR cut-off value of 9.07 was obtained to differentiate patients with mild severity and those with more severe disease. In conclusion, there is a correlation between the neutrophil-to-lymphocyte ratio and the severity of patients’ pneumonia.